Identification and analysis of poverty area in Kuala Perlis by using geographical information system application / Nada Shifaa Inani Rosli - Rosli, Nada Shifaa Inani (2020)
According to Statistic Department Malaysia, the government's intention in Malaysia's 10th Plan to reduce poverty from 3.8% in 2009 to 2.0% by 2015 and to boost the median household revenue from RM1, 440 in 2009 to RM3, 050 by 2015 by the highest 40% revenue (called B40). This study aims to identify the poverty area in Kuala Perlis, Perlis. The study uses secondary data from the Statistic Department and Coordination Unit (ICU) via e-Kasih portal system consisting of 398 heads of poor household in Kuala Perlis (Siti Zalikha Zahari, Chamhuri Siwar, Shaharudin Idrus, 2018). This research to show the poverty location in Kuala Perlis. This web can be used for donor to go to the poverty area. It is also help the donor to know the direction to poverty location in Kuala Perlis. This study uses ArcGIS software. Selected areas for this study are Kuala Perlis located in the state of Perlis. Kuala Perlis is the main focus for this study because it has a high proportion of poor and hard-core poor compared to other areas. The result shows that the poor in Kuala Perlis are mostly concentrated at Seberang Ramai village. The final result can be used by government employees, private employees and any donor who wishes to donate to those less fortunate in terms of income.